Pituitary adenylate cyclase-activating polypeptide plays a role in neuropsychiatric and substance use disorders: sex-specific perspective - Catherine E. Van Doorn; Mikala M. Zelows; Anel A. Jaramillo (Frontiers in Neuroscience)
The neuropeptide pituitary adenylate cyclase-activating peptide (PACAP) plays a pivotal role in regulating stress, fear, and anxiety responses. Genetic and molecular studies investigating PACAP demonstrate sex-dimorphic characteristics, with females exhibiting increased reactivity of PACAP signaling in neuropsychiatric disorders. Studies expand the role of PACAP to substance use disorders (SUD) by demonstrating modulation of PACAP can lead to neurobiological changes induced by nicotine, ethanol, stimulants and opioids. Given that females with SUD exhibit distinct drug use, relapse, and withdrawal sensitivity relative to males, we hypothesize that the PACAP system contributes to these sex-specific differences. Therefore, we review the role of PACAP in SUD by characterizing the role of PACAP at the molecular, brain regional, and behavioral levels relevant to the addiction cycle. We present literature linking PACAP to neuropsychiatric disorders, which demonstrate the intricate role of PACAP within neuronal signaling and pathways modulating addiction. We hypothesize that females are more particularly susceptible to PACAP-related changes during the intoxication and withdrawal phases of the addiction cycle. Altogether understanding the sex-specific differences in the PACAP system offers a foundation for future studies aimed at developing tailored interventions for addressing SUD.